Results of research work Russian society of oncomammologists “The use of artificial intelligence for early detection of breast cancer” - V. I. Pavlova; Yu. A. Belaya; A. Yu. Vorontsov; A. A. Prishchepov; S. M. Knyazev; A. A. Mikhaylov; A. V. Kovaleva; E. G. Arevshatyan; R. M. Paltuev; A. V. Chernaya; N. A. Zakharova (Опухоли женской репродуктивной системы, 2023)
Breast cancer is the most common cancer in women and one of the leading causes of death from cancer in Russia and most countries of the world. In countries with mammographic screening, there is a decrease in mortality from breast cancer. Introduction of mammographic image evaluation platforms into radiologist practice based on the work of artificial intelligence it allows not only to increase the coverage of the female population, but also to reduce the cost of screening, but it also increases the sensitivity and specificity of mammography as a method of breast cancer screening.The article presents the results of a study on the evaluation of mammographic images in women who have passed a preventive study using an artificial intelligence program.Within the framework of this project, mammographic images were analyzed using the service for viewing medical images “Celsus” in 8030 patients. The study assessed the age groups of 40-49 years, 50-59 years, 60 years and older. The average age of patients with suspected breast cancer was 54.8 years. Breast cancer was detected in 13 women (1.2 %), while the highest percentage of breast cancer was detected in the group with mammographic density D.